The glass pipeline: increasing supply chain synchronisation through information transparency. (1st September 2004) - Coleman, Julian; Lyons, Andrew; Kehoe, Dennis
Based upon a year-long project carried out at a UK luxury carmaker, this paper argues for a supply chain where upstream synchronisation is improved by the use of primary demand to calculate second and third-tier component requirements. The paper formulates a case for further developments to the established automotive "sequenced" supply model, where synchronised and lean first tiers are frequently supplied by lower tiers that carry higher stock levels, and whose production patterns bear little relationship to primary demand. The proposed development aims to enhance synchronisation of the lower portion of the chain that is outside the reach of full "sequenced" supply, but, within the time horizon of the vehicle manufacturers firm build schedule. This "synchronised" portion of the chain is achieved through increased information transparency, and hence the term "glass pipeline" has been used as a label for the proposed model. A case study illustration of the concept is presented, and a prototype is tested with a series of trials across a four-tier supply chain. A method for measuring synchronisation is developed, and associated business benefits are calculated in order to evaluate the model.